Interval-Valued Hesitant Fuzzy Prioritized Weighted Aggregation Operators for Multiple Attribute Decision Making. Issue 2 (June 2014) - Ye, Jun
The paper proposes an interval-valued hesitant fuzzy prioritized weighted averaging (IVHFPWA) operator and an interval-valued hesitant fuzzy prioritized weighted geometric (IVHFPWG) operator for aggregating interval-valued hesitant fuzzy information and investigates some properties of the proposed aggregation operators. Then, the IVHFPWA and IVHFPWG operators are utilized to develop two approaches for dealing with the interval-valued hesitant fuzzy multiple attribute decision making problems in which the attributes are in different priority level. Through the IVHFPWA or IVHFPWG operator and the score function of interval-valued hesitant fuzzy elements (IVHFEs), the ranking order of all alternatives can be determined and the best alternative can be easily identified as well. Finally, a practical example about talent introduction is given to demonstrate the practicality and effectiveness of the developed approaches.